A kind of biological hybrid material – Trichoderma viride/FeOOH as a durable anticorrosion coating for steel. (January 2023) - Tang, Congkui; Li, Shunling; Tan, Shuang; Liu, Chang; Yang, Xiaoqiang; Qu, Qing; Li, Lei
Graphical abstract: Highlights: A kind of biological nanomaterial by means of biological hybridization was synthesized. The bio-hybrid material was only 60 µm thick and had a very dense structure. The biological hybrid materials had a durable anticorrosion performance in artificial seawater. The corrosion resistance could still reach 87.45% after 20 d continuous immersion in seawater. Abstract: Development of anticorrosive materials is critical and the most efficient way in the innovation of solving corrosion problems. Biological hybrid materials have unique advantages and great potential in the corrosion resistance materials. Herein, a new biological hybrid material was designed by the interaction of Trichoderma viride ( T. viride ) and Fe-based nanomaterials for anticorrosion of steel in artificial seawater. The results showed that the biological hybrid material - T. viride /FeOOH with a cobweb was successfully synthesized by self-assembly of T. viride and Fe-based nanomaterials on the steel surface. T. viride /FeOOH with thickness only 60 μm exhibited good anti-corrosion effect and its anti-corrosion efficiency reached up to 88.97 %. Further, T. viride /FeOOH was fairly stable, and its corrosion resistance was still up to 87.45 % after 20 d of continuous immersion in seawater. This study provides a new perspective and option for anti-corrosion control of steel in marine environment.